Wilcoxon rank test for change in persistence. Issue 3 (4th May 2021) - Qin, Ruibing; Luo, Xinxin; Yang, Wei
Abstract : This paper proposes a test to detect the change in persistence on the basis of the ranks of a series, then derives the asymptotic distribution of the proposed test under the null hypothesis that a series is stationary, and the consistency of the test is established under the alternative hypothesis that a series shifts from I ( 0 ) to I ( 1 ) . The Monte-Carlo simulations demonstrate that the proposed test has less powers but more correct sizes in finite samples than the test proposed by Kim [Detection of change in persistence of a linear time series. J Econom. 2000;95(1):97–116], which means the test has a lower rejection rate than the Kim's test when the series is I ( 0 ) . As an illustration, we apply our test to the series of the monthly EXSDUS rate and the ISM non-manufacturing index in the United States.